A super-stable squaric acid-based metal-organic framework and a preparation method and application thereof
Patent Information
- Application Number
- CN202310286305.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-22
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2043-03-22
AI Technical Summary
但是,目前方酸基MOF的数量却相对有限,因为其合成条件苛刻且单一,UTSA-280和Co-squarate均是在碱性环境中合成,所以导致方酸基MOF的合成较为困难
[0027]1)本发明基于FJUT-3材料在室温和高温条件下的穿透实验证明其能够有效的从CO2/N2分离出CO2,且多次穿透循环测试表明FJUT-3稳定性好、分离效果显著、再生能力强。
Smart Images

Figure CN117551274B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of metal-organic framework materials technology, specifically relating to a low-cost, ultra-stable microporous metal-organic framework FJUT-3 material, its preparation method, and its application. Background Technology
[0002] Excessive greenhouse gas emissions leading to climate change have become a major threat to the global environment. Therefore, capturing and storing carbon dioxide from flue gas is a significant challenge. Simultaneously, the preferential adsorption and storage of carbon dioxide from both pre- and post-combustion processes is also crucial. Thus, preferential adsorption of carbon dioxide over nitrogen at high temperatures (313K-333K) is essential for post-combustion flue gas removal. Currently, CO2 removal primarily relies on aqueous amine solvents. While effective, this method suffers from significant drawbacks, including high production costs, energy-intensive regeneration, and chemical decomposition. This not only wastes resources but also threatens the environment. To address these challenges, adsorption separation technology has been proposed as an alternative due to its high efficiency and low energy consumption. The core material is the adsorbent, and various adsorbent materials, including zeolite and activated carbon, have been developed.
[0003] Unlike traditional zeolites and activated carbon, metal-organic frameworks (MOFs) are crystalline porous materials composed of inorganic nodes (metal ions / clusters) and organic linkers connected by coordination bonds. Due to their high modularity, unique porosity, and diverse functional groups, they have been proven to be potential porous materials for carbon dioxide adsorption. Among the many MOF materials, squaric acid-based MOFs exhibit excellent gas separation performance. For example, UTSA-280 (Nature Materials, 2018, 17(12): 1128-1133.) and Co-squarate (Journal of the American Chemical Society, 2019, 141(23): 9358-9364.) both use squaric acid (3,4-dihydroxy-3-cyclobutene-1,2-dione, SA) as their organic ligand, demonstrating outstanding performance in the separation of C2H4 / C2H6 and Xe / Kr, respectively. More importantly, they all exhibit good stability. Flue gas contains low concentrations of CO2 and most of N2, as well as some water and acidic gases. This necessitates that the adsorbent possess high water stability and acid resistance. In industrial applications, cost is also a crucial factor limiting the practical application of an adsorbent. Squaric acid-based MOFs utilize squaric acid as their organic ligand, which is inexpensive, costing only 1.396 × 10⁻⁶ kilograms. 3 The price of squaric acid-based MOFs is in US dollars. Therefore, they possess advantages such as high separation efficiency, low cost, and good stability. However, the current quantity of squaric acid-based MOFs is relatively limited because their synthesis conditions are demanding and singular. UTSA-280 and Co-squarate are both synthesized in alkaline environments, making the synthesis of squaric acid-based MOFs quite difficult. Furthermore, in order for adsorbents to be ultimately applied industrially to solve practical problems, in addition to the material's adsorption performance, production costs and the feasibility of large-scale synthesis must also be considered.
[0004] Therefore, developing a squaric acid-based MOF material with good separation performance, stability, cost, and scalability for carbon dioxide and nitrogen is of great significance and value for the industrial application of adsorbents for separating carbon dioxide and nitrogen. Summary of the Invention
[0005] To address the above problems, this invention provides a squaric acid-based MOF material constructed based on rare cuboethane-type tetranuclear metal cluster nodes. Unlike previous squaric acid-based MOFs, this material is synthesized under acidic conditions. Furthermore, this material can achieve highly efficient and selective adsorption and separation of carbon dioxide / nitrogen mixtures, and possesses advantages such as good stability, significant separation effect, low production cost, and the ability to be synthesized in large quantities.
[0006] To achieve the above objectives, the present invention provides the following technical solution:
[0007] A super-stable squaric acid-based metal-organic framework FJUT-3, with the general chemical formula [M4(μ3-OH)4(L1)3], wherein M is Co and the organic ligand L1 is squaric acid (3,4-dihydroxy-3-cyclobutene-1,2-dione, SA).
[0008] The structural formula of the organic ligand L1 is as follows:
[0009]
[0010] Furthermore, the FJUT-3 is a porous crystalline material formed by metal ions M and organic ligands L1 through coordination bonds.
[0011] Furthermore, the FJUT-3 crystallizes in a cubic crystal system with space group Fm-3m; its unit cell parameters are: α = β = γ = 90°.
[0012] Furthermore, each Co atom of the FJUT-3 is coordinated by three oxygen atoms of three μ3-OH and three different SA ligands, forming a typical octahedral coordination geometry.
[0013] In FJUT-3, four Co atoms are fixed together by four bridged μ3-OH atoms to form a cubane-type [Co4(μ3-OH)4] secondary building unit (SBU). Each [Co4(μ3-OH)4] secondary building unit (SBU) is connected to six adjacent [Co4(μ3-OH)4] secondary building units (SBU) through SA ligands to form a pcu topology type network framework FJUT-3 material.
[0014] After removing the guest molecule, FJUT-3 has a size of [missing information] along the three crystal axes. The aperture.
[0015] The preparation method of FJUT-3 mentioned above includes the following steps:
[0016] Weigh out cobalt metal salt and organic ligand L1, disperse them in a mixed solvent, and add tetrafluoroboric acid for acidification;
[0017] The mixed suspension was then reacted by solvothermal means, and then collected, washed, and vacuum dried to obtain the target product FJUT-3.
[0018] Furthermore, the cobalt metal salt is selected from any one of CoCl2·6H2O, CoSO4, Co(CH3COO)3, CoO, and Co(NO3)2.
[0019] Furthermore, the molar ratio of cobalt metal salt to organic ligand L1 is 4:3, and the mixed solvent is composed of N,N-dimethylacetamide, methanol, and tetrafluoroboric acid in a volume ratio of 15:5:2, wherein the tetrafluoroboric acid is a 40wt% aqueous solution; the suspension is heated at 100-130℃ and the reaction time is 315 days.
[0020] The metal-organic framework material used in this invention is a highly stable crystalline porous material prepared by a fluoride-containing modifier, consisting of metal ions and an organic ligand. Furthermore, the ligand used, squaric acid, is very inexpensive, costing only 1.396 × 10⁻⁶ kilograms. 3 The FJUT-3 compound, produced in US dollars, can be synthesized on a large scale, laying the foundation for mass production applications in industry. Furthermore, FJUT-3 exhibits excellent acid-base stability, and its highly polarized pore surface and suitable pore size facilitate the capture of carbon dioxide molecules, thereby achieving the separation of carbon dioxide and nitrogen.
[0021] Furthermore, the specific method by which FJUT-3 material is used for carbon dioxide / nitrogen separation is as follows:
[0022] When a mixture of carbon dioxide and nitrogen is brought into contact with activated FJUT-3 material, the activated FJUT-3 material selectively adsorbs the carbon dioxide gas, thereby achieving the separation of carbon dioxide and nitrogen.
[0023] Furthermore, the FJUT-3 material activation method includes the following steps:
[0024] The FJUT-3 material was exchanged in a low-boiling-point organic solvent a predetermined number of times, and then placed in a vacuum at 80-120℃ for 12-15 hours to remove the solvent until the vacuum reached 5 μmHg and remained unchanged, thus obtaining the activated FJUT-3 material.
[0025] The activated FJUT-3 material underwent CO2 adsorption testing at 195 K. Based on the CO2 adsorption isotherm at 195 K, the Brunauer-Emmett-Teller (BET) specific surface area of FJUT-3 was calculated to be 329 m². 2 g -1 Analysis of the CO2 adsorption isotherm at 195 K using the Horvath-Kawazoe (HK) method revealed that the calculated pore size distribution of FJUT-3 indicates an average pore size of [missing information]. Consistent with the results observed from the crystal structure, the activated FJUT-3 material was tested for gas adsorption performance of carbon dioxide (CO2) and nitrogen (N2) at 273 K, 298 K, 308 K, and 313 K. Based on the corresponding adsorption isotherms, the IAST values and Q values at different temperatures were calculated. stThe hydroxyl groups and squaric acid ligands in the metal cluster nodes [Co4(μ3-OH)4] of FJUT-3 material may have strong interactions with carbon dioxide molecules, preferentially capturing carbon dioxide molecules rather than nitrogen molecules. Therefore, this type of material follows the adsorption rule of CO2 > N2. For example, [Co4(μ3-OH)4(SA)3] (FJUT-3), calculated using ideal adsorption solution theory, has an adsorption selectivity of 178.30 for a binary CO2 / N2 (15 / 85 v / v) mixture at room temperature and pressure, and a selectivity of 139.27 at a high temperature of 313 K after flue gas combustion. Its CO2 / N2 breakthrough experiment has a duration of up to 50 min·g. -1 At 313K, the time also reached 29.4 min·g. -1 Furthermore, the breakthrough time remained almost unchanged after five cycles of testing, indicating that the material can effectively separate carbon dioxide and nitrogen mixtures, thereby achieving the goal of carbon dioxide capture. Moreover, by changing the synthesis conditions, approximately 1.16 g of sample can be obtained for adsorption testing in a single run. Considering its low synthesis cost, FJUT-3 achieves a balance between separation performance, stability, cost, and scalability, making it a promising candidate for industrial applications.
[0026] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0027] 1) Based on the breakthrough experiments of FJUT-3 material under room temperature and high temperature conditions, this invention proves that it can effectively separate CO2 from CO2 / N2, and multiple breakthrough cycle tests show that FJUT-3 has good stability, significant separation effect and strong regeneration ability.
[0028] 2) The synthesis method used in this invention has low cost and can be synthesized on a large scale, which can bring good economic benefits in industrial applications.
[0029] 3) This invention is an ultramicroporous MOF material constructed from cubane-type tetranuclear cobalt cluster [Co4(μ3-OH)4] structural units and small-sized organic ligand squaric acid. The high-nuclearity metal cluster nodes enable the entire framework of FJUT-3 to resist water and even acid and alkali corrosion, exhibiting good stability.
[0030] 4) This invention is based on the strong interaction between the hydroxyl groups and squaric acid ligands in the metal cluster nodes [Co4(μ3-OH)4] of the FJUT-3 material framework and carbon dioxide molecules. Such materials exhibit high selectivity for carbon dioxide molecules and can effectively separate carbon dioxide and nitrogen. The high CO2 / N2 separation performance, high stability, low cost, and large-scale synthesis characteristics of FJUT-3 make its future application in practical industries possible. Attached Figure Description
[0031] Figure 1 This is a schematic diagram of the crystal structure of the FJUT-3 material of the present invention.
[0032] Figure 2 This is a comparison of the PXRD patterns of the crystal FJUT-3 of the present invention after soaking in solutions with different pH values with the original PXRD patterns.
[0033] Figure 3 This is a comparison of the original PXRD pattern of the crystal FJUT-3 of the present invention after soaking in water for 40 days.
[0034] Figure 4 This is a comparison diagram of the original PXRD pattern of a sample of FJUT-3 crystal expanded to about 1g.
[0035] Figure 5 The CO2 adsorption isotherm of the crystal FJUT-3 of the present invention at 195K is shown, and its pore size distribution is calculated using the HK method.
[0036] Figure 6 The adsorption isotherms of carbon dioxide for the crystal FJUT-3 of the present invention at 273K, 298K, 308K and 313K are shown.
[0037] Figure 7 The adsorption isotherms of nitrogen gas in the crystal FJUT-3 of this invention at 273K, 298K, 308K and 313K are shown.
[0038] Figure 8 The IAST selectivity curve and corresponding adsorption isotherm of the crystal FJUT-3 of the present invention at 298K are shown.
[0039] Figure 9 The IAST selectivity curve and corresponding adsorption isotherm of the crystal FJUT-3 of the present invention at 308K are shown.
[0040] Figure 10 The IAST selectivity curve and corresponding adsorption isotherm of the crystal FJUT-3 of the present invention at 313K are shown.
[0041] Figure 11 This is a comparison of the CO2 adsorption isotherms at 298 K between the expanded sample of the crystal FJUT-3 of the present invention and the original sample.
[0042] Figure 12 This refers to the CO2 and N2 adsorption enthalpy of the crystal FJUT-3 of the present invention.
[0043] Figure 13 This is the breakthrough curve of the crystal FJUT-3 of the present invention in a CO2 / N2 (15:85, v / v) mixed gas at room temperature and pressure.
[0044] Figure 14 The image shows the multiple penetration curves of the crystal FJUT-3 of this invention in a CO2 / N2 (15:85, v / v) mixed gas at room temperature and pressure.
[0045] Figure 15 The transmission curves of the crystal FJUT-3 of the present invention in a CO2 / N2 (15:85, v / v) mixed gas under multiple temperature gradients are shown.
[0046] Figure 16 The image shows the multiple penetration curves of the crystal FJUT-3 of this invention in a CO2 / N2 (15:85, v / v) mixed gas at 313K. Detailed Implementation
[0047] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0048] See attached document Figure 1 As shown, FJUT-3 is an ultraporous MOF material with a three-dimensional PCU structure based on cubic tetranuclear Co cluster nodes. It is a porous crystalline material with the general chemical formula [M4(μ3-OH)4(L1)3], formed by coordination bonds between metal ions M and organic ligand L1, where M is Co and L1 is squaric acid (3,4-dihydroxy-3-cyclobutene-1,2-dione, SA). FJUT-3 crystallizes in a cubic crystal system with space group Fm-3m; its unit cell parameters are: α=β=γ=90°. Each Co atom in FJUT-3 is coordinated by three oxygen atoms of three μ3-OH and three different SA ligands, forming a typical octahedral coordination geometry;
[0049] In FJUT-3, four Co atoms are fixed together by four bridged μ3-OH atoms, forming a cubane-type [Co4(μ3-OH)4] secondary building unit (SBU). Each [Co4(μ3-OH)4] secondary building unit (SBU) is connected to six adjacent [Co4(μ3-OH)4] secondary building units (SBU) through SA ligands, forming a pcu topology-type network framework FJUT-3 material. After removing the guest molecules, FJUT-3 has a size of [missing information] along the three crystal axes. The aperture.
[0050] Example 1:
[0051] The preparation method of [Co4(μ3-OH)4(SA)3](FJUT-3) crystals includes the following steps:
[0052] Weigh out 0.095 g (0.4 mmol) of CoCl2·6H2O and 0.034 g (0.3 mmol) of 3,4-dihydroxy-3-cyclobutene-1,2-dione (SA) into a 20 mL glass bottle. Add N,N-dimethylacetamide (3 mL) / methanol (1 mL) solvent to the glass bottle and sonicate for 30 min. Then add 400 μL of HBF4 (tetrafluoroboric acid, 40 wt% aqueous solution) for acidification. Finally, seal the mixed suspension and keep it in a circulating oven at 120 °C for 3 days. Then collect, wash and vacuum dry to obtain the target product, red cubic crystals FJUT-3.
[0053] FJUT-3 crystals are immersed in methanol solvent, and the solvent is changed every 12 hours. After six changes, they are activated in a vacuum at 120°C for 12 hours to obtain FJUT-3 crystals that can be used for adsorption testing.
[0054] Example 2:
[0055] The preparation method of expanded [Co4(μ3-OH)4(SA)3](FJUT-3) crystals includes the following steps:
[0056] Weigh out 1.9 g (8 mmol) of CoCl2·6H2O and 0.685 g (6 mmol) of 3,4-dihydroxy-3-cyclobutene-1,2-dione (SA) into a 60 mL glass bottle. Add N,N-dimethylacetamide (40 mL) / methanol (15 mL) solvent to the glass bottle and sonicate for 50 min. Then add 4 mL of HBF4 (tetrafluoroboric acid, 40 wt% aqueous solution) for acidification. Finally, seal the mixed suspension and keep it in a circulating oven at 120 °C for 3 days. Then collect, wash and vacuum dry to obtain the target product, red cubic crystals FJUT-3.
[0057] The expanded amount of FJUT-3 crystals was immersed in methanol solvent, and the solvent was changed every 12 hours. After eight changes, it was activated in vacuum at 120℃ for 15 hours to obtain the expanded amount of FJUT-3 crystals that can be used for adsorption testing.
[0058] See attached document Figure 2 As shown, the PXRD patterns of FJUT-3 material in solutions with different pH values did not change significantly from the original PXRD patterns, proving that no phase transition or structural collapse occurred. This indicates that FJUT-3 has high acid and alkali stability.
[0059] See attached document Figure 3 As shown, the PXRD pattern indicates that the pattern of FJUT-3 material after immersion in water for 40 days did not change significantly compared with the original pattern, indicating that FJUT-3 has high water stability.
[0060] See attached document Figure 4 As shown, the PXRD pattern indicates that the PXRD pattern of FJUT-3 material at a scaled-up amount of about 1g did not show significant changes compared to the original pattern, demonstrating the reliability of FJUT-3 in large-scale production.
[0061] See attached document Figure 5 As shown, based on the CO2 adsorption isotherm at 195 K, the BET specific surface area of FJUT-3 was calculated to be 329 m². 2 g -1 Analysis of the CO2 adsorption isotherm at 195 K using the HK method revealed that the calculated pore size distribution indicates that the average pore size of FJUT-3 is [missing information]. Consistent with the results observed from the crystal structure.
[0062] See attached document Figure 6-7 As shown, the adsorption isotherms of carbon dioxide and nitrogen gases by FJUT-3 at 273K, 298K, 308K and 313K indicate that under the same test conditions, despite different temperatures, even at a high temperature of 313K after flue gas combustion, the adsorption capacity of CO2 by FJUT-3 is much higher than that of N2, indicating that FJUT-3 can effectively separate carbon dioxide and nitrogen.
[0063] See attached document Figure 8-10 As shown, the adsorption data of carbon dioxide and nitrogen gases by FJUT-3 at 298 K, 308 K and 313 K were calculated using the ideal solution adsorption theory. The results show that the adsorption selectivity of FJUT-3 for CO2 / N2 (15:85, v / v) mixed gas is 178.3, 126.4 and 139.2 under the conditions of 298 K, 308 K and 313 K and 100 kPa.
[0064] See attached document Figure 11 As shown, CO2 adsorption tests were conducted at 298 K using an expanded amount of FJUT-3 sample. After comparing the CO2 adsorption isotherm at 298 K with that of the original sample, the trend and adsorption amount were basically consistent with those of the original sample, proving the reliability of the expanded amount sample.
[0065] See attached document Figure 12 As shown, based on the adsorption isotherms of CO2 and N2 at different temperatures (273 and 298 K), the zero-loading Q of CO2 in FJUT-3 was calculated using the Clapeyron equation. stThe value is 41.69 kJ·mol -1 Q is much larger than its N2 st Value 16.42 kJ·mol -1 .
[0066] See attached document Figure 13 As shown, a gas-mixed breakthrough experiment was conducted at room temperature and pressure, with a CO2 / N2 (15:85, v / v) gas mixture being introduced at a rate of 2 mL / min. -1 The total flow rate was injected into the packed column containing activated FJUT-3. The breakthrough curves showed that N2 gas penetrated the packed column immediately, while CO2 gas did not penetrate until 50 min·g. -1 It was only detected later. This result indicates that the activated FJUT-3 can effectively separate CO2 from a CO2 / N2 (15:85, v / v) mixture using a packed column.
[0067] See attached document Figure 14 As shown, the stability and recyclability of activated FJUT-3 were evaluated through multiple breakthrough experiments. The activated FJUT-3 could re-adsorb after five cycles without a significant decrease in adsorption capacity, indicating that the material has good regenerability in CO2 / N2 separation.
[0068] See attached document Figure 15 As shown, mixed gas breakthrough experiments were conducted at temperature gradients of 308 K, 313 K, 323 K, and 333 K, with the CO2 / N2 (15:85, v / v) mixed gas being introduced at a rate of 2 mL / min. -1 The total flow rate was injected into the packed column containing activated FJUT-3, and the breakthrough curve showed a corresponding breakthrough time of 37.39 min·g. -1 29.40 min·g -1 23.03 min·g -1 and 19.85 min·g -1 This result demonstrates that the activated FJUT-3 can effectively separate CO2 from a CO2 / N2 (15:85, v / v) mixture even at high temperatures using a packed column.
[0069] See attached document Figure 16 As shown, the stability and recyclability of activated FJUT-3 were evaluated through multiple breakthrough experiments at 313 K. The activated FJUT-3 could re-adsorb after five cycles without a significant decrease in adsorption capacity, indicating that the material still exhibits good regenerability for CO2 / N2 separation at the high temperature of 313 K after flue gas combustion, meeting the requirements of practical industrial applications.
[0070] The above embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit it. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A superstable squaric acid-based metal-organic framework FJUT-3, characterized in that, The general chemical formula is [M4(µ3-OH)4(L1)3], where M is Co and the organic ligand L1 is 3,4-dihydroxy-3-cyclobutene-1,2-dione; FJUT-3 is a porous crystalline material formed by coordination bonds between metal ions M and organic ligand L1; FJUT-3 crystallizes in a cubic crystal system with space group [space group number missing]. Fm-3m Its unit cell parameters are: a=b=c=18.9619(3)Å, α=β=γ=90°; Each Co atom of FJUT-3 is coordinated by three oxygen atoms of three µ3-OH and three different SA ligands, forming a typical octahedral coordination geometry. In FJUT-3, four Co atoms are anchored together by four bridged µ3-OH atoms, forming a cubane-type [Co4(µ3-OH)4] secondary building unit. Each [Co4(µ3-OH)4] secondary building unit is connected to six adjacent [Co4(µ3-OH)4] secondary building units via SA ligands. pcu Topology type network framework FJUT-3 material; After the guest molecules are removed, FJUT-3 has a pore size of 4.7 Å along the three crystal axes.
2. The ultrastable squaric acid-based metal-organic framework FJUT-3 according to claim 1, characterized in that, The preparation method of FJUT-3 includes the following steps: Weigh out cobalt metal salt and organic ligand L1, disperse them in a mixed solvent, and add tetrafluoroboric acid for acidification; The mixed suspension was then reacted by solvothermal means, and then collected, washed, and vacuum dried to obtain the target product FJUT-3.
3. The ultrastable squaric acid-based metal-organic framework FJUT-3 according to claim 2, characterized in that, The cobalt metal salt is selected from any one of CoCl2·6H2O, CoSO4, Co(CH3COO)3, CoO, and Co(NO3)2.
4. The ultrastable squaric acid-based metal-organic framework FJUT-3 according to claim 2, characterized in that, The molar ratio of cobalt metal salt to organic ligand L1 is 4:
3. The mixed solvent is composed of N,N-dimethylacetamide, methanol, and tetrafluoroboric acid in a volume ratio of 15:5:2, wherein the tetrafluoroboric acid is a 40wt% aqueous solution. The suspension is heated at 100~130℃ and the reaction time is 3~5 days.
5. An application of the ultra-stable squaric acid-based metal-organic framework material FJUT-3 as described in any one of claims 1-4, characterized in that, The FJUT-3 material is used for the separation of carbon dioxide and nitrogen.
6. The application of the ultra-stable squaric acid-based metal-organic framework material FJUT-3 according to claim 5, characterized in that, The specific method by which FJUT-3 material is used for carbon dioxide / nitrogen separation is as follows: When a mixture of carbon dioxide and nitrogen is brought into contact with activated FJUT-3 material, the activated FJUT-3 material selectively adsorbs the carbon dioxide gas, thereby achieving the separation of carbon dioxide and nitrogen.
7. The application of the ultra-stable squaric acid-based metal-organic framework material FJUT-3 according to claim 6, characterized in that, The activation method for the FJUT-3 material includes the following steps: The FJUT-3 material was exchanged in a low-boiling-point organic solvent a predetermined number of times, and then placed in a vacuum at 80~120℃ for 12~15h to remove the solvent until the vacuum reached 5μmHg and remained unchanged, thus obtaining the activated FJUT-3 material.